Russia-NATO-US: from detente to impossible cooperation (1999-2019) - Francesco Randazzo (Palgrave MacMillan, 2022)
Born with a clearly anti-Soviet purpose, NATO was compelled to redefine its goals and strategies following the end of the Cold War in the late 1980s and early 1990s. In this new context, the North Atlantic organisation attempted to view Russia as a potential partner while still pursuing a policy of military interventionism and expansion into Eastern Europe—a strategy that Moscow consistently viewed with suspicion. After the attacks of 11 September 2001, the temporary cooperation between NATO and Russia in the fight against terrorism gradually gave way to renewed divisions, fuelled by American unilateralism and Russia’s revived ambitions as a great power. The Russo-Ukrainian conflict may mark either the beginning of a new international rivalry or the culmination of a relationship that has reached its limit and is now in need of transformation. How, where, and when this renewal will occur are questions to which we historians cannot provide answers, as foresight is not within our skill set.However, if NATO’s eastern expansion and militarisation were intended to strengthen European security, it is clear that this objective has not been achieved. Today, Europe is the stage of the largest military conflict since the end of the Second World War, and it stands closer to a generalised confrontation than at any time in the post-war era. Whether the war between Russia and Ukraine will foreshadow a new “shot heard in Sarajevo” as it was in the previous century, only time will tell.